2017
DOI: 10.1002/cncy.21831
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and assuring quality performance in cytology: A toolkit

Abstract: The cytology community has long been at the leading edge of quality assurance and quality control in anatomic pathology. However, with the increasing burden of clinical care, daily operations, and regulatory compliance, quality management risks becoming just another box to check on a long list of onerous tasks. To begin to address these issues, this article will focus primarily on “proactive” quality improvement, covering quality metric selection and monitoring, and outlines how to determine when to act on dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…TCT is capable of identifying patients with cytology abnormality and inflammation, and it can determine if these patients are at a high risk of cytology abnormality. Previous studies found that inflammation as an initiation and carcinogenesis factor is positively correlated to the cervical cancer [31]. Our results revealed that, mild and moderate inflammation had no significant difference between cytological abnormality and control (P>0.05), while the incidence of severe inflammation was significantly higher in cytological abnormality than in the control (P<0.05) ( Figure 5A).…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…TCT is capable of identifying patients with cytology abnormality and inflammation, and it can determine if these patients are at a high risk of cytology abnormality. Previous studies found that inflammation as an initiation and carcinogenesis factor is positively correlated to the cervical cancer [31]. Our results revealed that, mild and moderate inflammation had no significant difference between cytological abnormality and control (P>0.05), while the incidence of severe inflammation was significantly higher in cytological abnormality than in the control (P<0.05) ( Figure 5A).…”
Section: Discussionsupporting
confidence: 41%
“…In our study, the satisfaction rate of TCT was high up to 96.16 % (46255/48101). According to the analysis of the problems of the unsatisfactory slides, it's necessary to standardize operational details: a) collect enough epithelial cells for observation with cotton swabs; b) wipe the secretion after rub-up to brush into the cervix; c) use the voyeuristic for fully exposed cervix; d) contact sufficiently the surface of cervical squamous epithelium and transition zone with cervical cells brush for 8-10 circles at the same direction [31]. It's recommended that sampling is performed by skilled and experienced gynecologists.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be helpful in predicting possible errors with time. Heher et al [17] also concluded that proactive quality improvement in cytology includes quality tools such as quality charts, Andon signals, and visual quality dashboards.…”
Section: Discussionmentioning
confidence: 99%
“…Within either of these frameworks (hand written logs or dedicated reports from the LIS), some authors have looked to the clinical laboratory for ways to improve the utility of this data. 3 A common approach is to separate preanalytic, analytic, and postanalytic processes and to use variants of Levey-Jennings plots to continuously document performance that is within and outside of acceptable ranges. This approach has already been shown to lead to some success, in particular with clinicians who are providing suboptimal specimens.…”
Section: Current Practicementioning
confidence: 99%